2015
DOI: 10.1080/01436597.2015.1048797
|View full text |Cite
|
Sign up to set email alerts
|

Patronage, politics and performance: radio call-in programmes and the myth of accountability

Abstract: The role of media in promoting political accountability and citizen participation is a central issue in governance debates. Drawing on research into the interactions between radio station owners, journalists, audiences and public authorities during Somali radio call-in programmes we argue that these programmes do not simply offer a new platform for citizens to challenge those who are governing but that they are also spaces where existing power structures reproduce themselves in new forms. We identify the ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Inducement to wrong by bribery or other unlawful or improper means (n=1) Choudrie et al 2017, Goundar 2009, Introna et al 2010, Krishnan and Teo 2012, Lee and Lio 2016, Masiero 2015, Owusu-Oware et al 2018, Palvia et al 2017, Pankowska 2017, Peterson 1998, Priyatman 2008, Raghupathi and Wu 2011, Rana et al 2013, Rana et al 2014, Senyo et al 2019, Seo and Warman 2011, Silva and Hirschheim 2007, Srivastava et al 2007, Stamati et al 2015, Stremlau et al 2015, Therese and Azwe 2016, Vaidya and Myers 2017, Veeraraghavan 2013, Zhao and Xu 2015 For example, the definition relies on a clear distinction between 'public' and 'private' although in the context of several developing countries, particularly those in Africa, it has been shown that the lines between public and private are at best blurred and at worst non-existent (Nawaz & Hodess, 2008;O'Neil, 2007;von Soest, 2006).…”
Section: Sahay and Puri 2008mentioning
confidence: 99%
See 2 more Smart Citations
“…Inducement to wrong by bribery or other unlawful or improper means (n=1) Choudrie et al 2017, Goundar 2009, Introna et al 2010, Krishnan and Teo 2012, Lee and Lio 2016, Masiero 2015, Owusu-Oware et al 2018, Palvia et al 2017, Pankowska 2017, Peterson 1998, Priyatman 2008, Raghupathi and Wu 2011, Rana et al 2013, Rana et al 2014, Senyo et al 2019, Seo and Warman 2011, Silva and Hirschheim 2007, Srivastava et al 2007, Stamati et al 2015, Stremlau et al 2015, Therese and Azwe 2016, Vaidya and Myers 2017, Veeraraghavan 2013, Zhao and Xu 2015 For example, the definition relies on a clear distinction between 'public' and 'private' although in the context of several developing countries, particularly those in Africa, it has been shown that the lines between public and private are at best blurred and at worst non-existent (Nawaz & Hodess, 2008;O'Neil, 2007;von Soest, 2006).…”
Section: Sahay and Puri 2008mentioning
confidence: 99%
“…Table 5 summarizes motivations underpinning digitalization and corruption in the literature. (Addo, 2016;Amankwah-sarfo, Boateng, & Effah, 2018;Kock & Gaskins, 2013;Senyo, Liu, & Effah, 2019b), or be tactical i.e., have short-term expectations derived from a general belief in the potential of digital technologies to transform organization (Stremlau, Fantini, & Gagliardone, 2015).…”
Section: Anti-corruption Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, models are most often challenged by hybrid realities (e.g. Gagliardone, 2015; Stremlau et al, 2015; Willems, 2013), in which several contradictory types of communication are at play. Media actors frequently use descriptors such as ‘community media’ strategically to position themselves in uncertain and power-striated environments (see Brisset-Foucault, 2011).…”
Section: From Labels To Context To Practices: Articulating An Urban Pmentioning
confidence: 99%